Digital village innovation during the COVID-19 pandemic in Nusa Jaya District - Dini Mauludiawati; Toddy Aditya; Achmad Kosasih; Achmad Chumaedi; Slamet Setiawan (Publisia: Jurnal Ilmu Administrasi Publik, 2023)
The purpose of this study was to determine digital adoption in the Nusa Jaya Village, Karawaci District, Tangerang City. The Nusa Jaya Village made a breakthrough or innovation in their public services by utilizing and optimizing ICT in digitalization, Namely the application of pangkas applications. This study uses qualitative and descriptive methods for the phenomenon of e-government adoption in Nusa Jaya Village. Several factors influence e-government adoption which is one of the success factors of e-government, namely: Advantage (success) with the existence of a pruning application, the community is assisted in the process of making documents and other bureaucratic services, Trust (Trust) where the community has confidence in sites/applications where people are not worried about personal data leaks where there are policies that cover them, Internet Accessibility (Internet Accessibility) the quality of internet access itself has good access speed although there are some that are still hampered by their internet network the ability of the community to access internet services such as websites , e-mail. Internet Skills, which are still an obstacle and a challenge in the Nusa Jaya sub-district, apart from being constrained by limited competent human resources, knowledge, education and a lack of ability in the use and utilization of IT. There are still many people who are clueless, so it is difficult to socialize and train the application so that socialization must be carried out regularly and training needs to be increased again and not all people have smartphones.